2013
DOI: 10.1044/1058-0360(2012/11-0004)
|View full text |Cite|
|
Sign up to set email alerts
|

The Contribution of Two Categories of Parent Verbal Responsiveness to Later Language for Toddlers and Preschoolers on the Autism Spectrum

Abstract: Purpose Longitudinal associations between two categories of parent verbal responsiveness and language comprehension and production one year later were examined in 40 toddlers and preschoolers with a diagnosis of an autism spectrum disorder (ASD). Method Parent-child play samples using a standard toy set were digitally captured and coded for child engagement with objects and communication acts and for parent verbal responses to play and communication. Results After controlling for parent education, child en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 46 publications
(92 reference statements)
6
101
0
Order By: Relevance
“…Specifically, mothers' use of follow-in comments predicted language comprehension 1 year later for children who were initially minimally verbal, but this was not related to later language skills for children who initially had higher level language skills. However, regardless of the child's initial language level, Haebig et al (2013) found that parents' use of follow-in-directives for language (i.e., directing the child to respond verbally about the child's current focus of attention) accounted for unique variance in later language comprehension and expression. Given that fathers tend to use more directive language than mothers overall (Gleason, 1975;Goldberg et al, 2002;Masur & Gleason, 1980), it may have been the case in the current study that paternal verbal responsiveness included more follow-in directives than maternal verbal responsiveness and that follow-in directives helped promote child language development across the wide range of language levels represented in this study (from minimally verbal to verbally fluent).…”
Section: Future Directionsmentioning
confidence: 93%
“…Specifically, mothers' use of follow-in comments predicted language comprehension 1 year later for children who were initially minimally verbal, but this was not related to later language skills for children who initially had higher level language skills. However, regardless of the child's initial language level, Haebig et al (2013) found that parents' use of follow-in-directives for language (i.e., directing the child to respond verbally about the child's current focus of attention) accounted for unique variance in later language comprehension and expression. Given that fathers tend to use more directive language than mothers overall (Gleason, 1975;Goldberg et al, 2002;Masur & Gleason, 1980), it may have been the case in the current study that paternal verbal responsiveness included more follow-in directives than maternal verbal responsiveness and that follow-in directives helped promote child language development across the wide range of language levels represented in this study (from minimally verbal to verbally fluent).…”
Section: Future Directionsmentioning
confidence: 93%
“…Participants were 63 children (55 males) with ASD with a mean age of 45 months ( SD = 3.94, Range = 37 - 53) recruited as part of a larger longitudinal study (Ellis Weismer et al, 2011; Haebig, McDuffie, & Ellis Weismer, 2013a, 2013b; Ray-Subramanian & Ellis Weismer, 2012; Ray-Subramanian, Huai, & Ellis Weismer, 2011; Venker, Eernisse, Saffran, & Ellis Weismer, 2013) examining language development in toddlers and preschoolers with ASD. Participants in the larger longitudinal study were recruited through local early intervention programs, developmental medical clinics, and posted fliers and magazine and newspaper advertisements in the state of Wisconsin.…”
Section: Methodsmentioning
confidence: 99%
“…Past work has demonstrated that parent linguistic responses to child leads are associated with later receptive language in children with ASD who are in the early stages of language development (Haebig, McDuffie, & Weismer, 2013a; 2013b; BLINDED et al, 2015). Studies have additionally shown links for early attention to child directed speech and intentional communication with later receptive language in this population (BLINDED et al, 2015).…”
Section: Why Receptive Vocabulary Might Be a Mediator For The Predictmentioning
confidence: 99%